PARTISIPASI PEREMPUAN DALAM OLAHRAGA PERSPEKTIF HERMENEUTIKA HADIS FAZLUR RAHMAN - Rianto Hasan (UIN Sunan Kalijaga Yogyakarta, 2019)
Muslim society perception of gender issues are influenced and constructed based on their religious understanding. Oftentimes, controversy arises because of difference in perspective regarding the discussion. One of factual problem that is often questioned is the discourse about women's participation in the sport. Therefore this paper was made by making the above polemic as an academic problem that was answered based on the epistemological fundamental of the hadith, specifically using the Fazlur Rahman’s hermeneutic method of Hadith. From the research that has been done it was found that Islam affirms sporting activity for women both the activity is carried out as an ordinary physical routine, and it is occupied as a field of work as a female athlete whose pioneering sport activity for self-career development. This validity is obtained by women with several prerequisites : 1). Comply with religious norms, decency, and other consideration such as medical procedure in their activity so as to avoid the emergence of adverse effect or loss-material and immaterial-to personal and other people. 2). Balancing the division of time between sport activity and other routines that also have crucial value. Keyword: hermeneutic, Hadith, Fazlur Rahman, Gender, Sport